Upaya Meningkatkan Hasil Belajar IPA menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Berbantuan Media Alat Peraga Konkret pada Peserta Didik Kelas V SDN-4 Kasongan Baru Tahun Pelajaran 2016/2017: Efforts to Improve Learning Outcomes of Science using the Jigsaw Cooperative Learning Model with the Assistance of Concrete Teaching Media in Class V Students of SDN-4 Kasongan New 2016/2017 Academic Year - Cici Liana Fitriana; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to (1) find out about the activities of students in learning activities by using a cooperative type jigsaw model assisted with concrete teaching aids (2) knowing the improvement in student learning outcomes in science learning in matter Gravity force, friction force and magnetic force with using a cooperative type jigsaw model assisted with concrete teaching aids in class V of the Kasongan New SDN-4 Academic Year 2016/2017. The type of research is Class Action Research (CAR), the research subjects were 18 students, six men, and 12 women. The technique for collecting data uses observation and test techniques. This study uses analysis and the average and percentage of completeness taken from the results of the learning cycle.